2015
DOI: 10.1016/j.gca.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and roles of solution and surface species of chalcopyrite dissolution at 650 mV

Abstract: To better understand chalcopyrite dissolution in hydrogeochemical processes and the related environmental issue of acid and metalliferous drainage (AMD), the kinetics as well as the influence of solution composition and the nature of surface species formed during chalcopyrite dissolution have been examined under the controlled conditions of E h 650 mV (SHE), pH 1.0-2.0 and 75°C, with/without 4 mM Fe 2+ addition. SEM and XPS analyses indicate that the surface products, both at micro-and nano-scales, did not pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 86 publications
2
23
0
Order By: Relevance
“…The presence of a small portion of SO 4 2− indicated that chalcopyrite surface was weekly oxidized by air during grinding or drying process. However, it was reduced to 2 % S and 3 % S when chalcopyrite was treated in 0.01 M CaCl 2 and 0.05 M MgCl 2 solutions, respectively, due possibly to the dissolution of sulfate from chalcopyrite surface into solution [48]. In addition, further decrease was observed when 10 mg/L SHMP was added, indicating that the addition of SHMP was beneficial to SO 4 2− dissolution.…”
Section: S 2p Spectramentioning
confidence: 96%
See 2 more Smart Citations
“…The presence of a small portion of SO 4 2− indicated that chalcopyrite surface was weekly oxidized by air during grinding or drying process. However, it was reduced to 2 % S and 3 % S when chalcopyrite was treated in 0.01 M CaCl 2 and 0.05 M MgCl 2 solutions, respectively, due possibly to the dissolution of sulfate from chalcopyrite surface into solution [48]. In addition, further decrease was observed when 10 mg/L SHMP was added, indicating that the addition of SHMP was beneficial to SO 4 2− dissolution.…”
Section: S 2p Spectramentioning
confidence: 96%
“…In other words, SHMP reduced the formation and adsorption of Mg(OH) 2 on chalcopyrite, thereby improving chalcopyrite recovery. Figure 10 shows five S species including monosulfide (S 2− ), disulfide (S 2 2− ), polysulfide (S n 2− ), sulfate (SO 4 2− ) and an energy loss feature (S 3p → Fe 3d) located at 161.3 eV, 162.0 eV, 162.8 eV, 169.1eV and 164.9 eV, respectively [38,[46][47][48][49].…”
Section: Survey Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Further study has shown that the chacopyrite dissolution rate at 650 mV is increased in the presence of added soluble iron [20]. However, the effect of pyrite at these two Eh conditions (i.e., 650 and 750 mV SHE) is not yet well understood.…”
Section: Introductionmentioning
confidence: 98%
“…As some previous research works regarding chalcopyrite leaching were conducted in a sulfuric acid system [19,29,30], the adsorption sites of the SO4 2− and cations would play a role in chalcopyrite dissolution.…”
Section: Adsorption Sitesmentioning
confidence: 99%